ANALISIS PENGARUH BAURAN PEMASARAN UNTUK MENINGKATKAN PENJUALAN MOBIL NISSAN PADA PT. WAHANA WIRAWAN INDOMOBIL NISSAN MALANG - Zakia Ilhami; Agus Widarko; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
AbstractEvery company will always compete in seizing market share. For that theentrepreneurs must be good at influencing consumers to want to use the productsproduced by each company. To be able to do so requires good management,strategy and human resources within the company. A company has several goalsto be achieved, both short-term goals and long-term goals. In the short termusually to win the hearts of consumers especially for newly launched products.While in the long term done to maintain existing products in order to remainmarketable and can compete.This research was conducted at PT. Wahana Wirawan Indomobil NissanMalang. The purpose of this study is to know and analyze the influence ofmarketing abauran consisting of product, price, promotion and place tosimultaneous increase of sales. This type of research is a quantitative research.Respondents in this study are consumers of PT. Wahana Wirawan IndomobilNissan Malang. Population in this research is consumer of PT. Wahana WirawanIndomobil Nissan Malang for one month, amounting to 300 consumers, thesample in this study using Slovin formula that amounted to 75 employees orrespondents. Data collection method used is to spread the questionnaire andinterview. The results showed that product, price, promotion, and place variablessimultaneously affect the sales of Nissan cars at PT. Wahana Wirawan IndomobilNissan Malang.Keywords: sales, product, price, promotion, place